Genome editing and selection based on genes associated with sports athletic performance : some bio-ethical issues - Zajc Petranović, Matea (Array, 2020)
In 2003 the final results of the Human Genome Project revealed the details of our genome: a set of information about how human beings look, how we act, feel, think and develop. Soon after, other global collaborations such as the HapMap project and 1000 Genomes Project were conducted. Although the main focus was to investigate the variability in human populations and the possible connections of certain variations to different conditions and diseases, these projects also had a great impact on the understanding of the genetic influence on sports performance. In parallel, improved methods for gene analysis and gene editing were developed. Based on those methods, it became possible to detect candidate genes responsible for different performance phenotypes and develop protocols similar to gene therapies for performance enhancement in athletes. This review covers developments in genetics, the overview of candidate genes associated with athletic performance, and ethical dilemmas related to the modification of genome for sport performance enhancement.